Perbedaan Prestasi Belajar Siswa Kelas VII SMPN 7 Malang yang Menggunakan Modul IPA Terpadu dengan Model Pembelajaran Integrasi Tema Pemuaian Pada Berbagai Wujud Zat. - Kartika Wulandari; Khusnul Khotimah (JoEMS (Journal of Education and Management Studies), 2019)
To support Integrated Science learning, an integrated learning resource is needed, so that harmony between learning models and learning resources is created, namely the Integrated Science module. Based on this, it was tried to apply the module on Integrated Science learning with the hypothesis that students 'learning achievements taught with Integrated Science modules with integrated learning models with high initial abilities were better than students' learning achievements taught without Integrated Science modules with high initial abilities and also vice versa. The purpose of applying this module is to find out the differences in student achievement. The research method used is a quantitative approach with a type of quasi-experimental research with different treatments in both samples. The class used is 7A as an experiment and 7B as a control class. For the experimental class learning activities are accompanied by modules with integration learning models, while the control class is without modules. Then to test the hypothesis used ANOVA AB Statistical Test followed by Scheffe Test. Students' abilities are distinguished from the class average, if above the class average is called high ability and vice versa. From the results of the two post test classes, the average experimental class = 65.11> 51.44 (control class). While the ANOVA Statistics results obtained thitung = 5.002> 2.01575 (t45; .05) which means that student learning achievement taught with Integrated Science module with integrated learning models with high initial abilities is better than students' learning achievement taught without modules Integrated Science with high initial ability with experimental class average = 66.38> 54.29 (control class). Whereas for students with low initial abilities, the results of tcount = 6.34> 2.0231 (t39; .05) means that students 'learning achievements taught with Integrated Science modules with integration learning models with low initial abilities are better than students' learning achievements. taught without an Integrated Science module with a low initial ability with an experimental class average = 63.9> 47.54 (control class). It can be said that the module is suitable for students with high initial abilities as well as students with low initial abilities.